Discouraged worker effects and barriers against employment for immigrant and non-immigrant women - John K. Dagsvik; Tom Kornstad; Terje Skjerpen (Statistics Norway, Research Department, 2016)
A phenomenon observed in many labor markets is that the supply of labor appears to depend on business cycles. In other words, workers who are searching for work become "discouraged" under unfavorable business cycle conditions because they believe that their chances of finding an acceptable job are so small that the costs of searching for work outweigh the benefits from searching. In this paper we present a new theoretical framework for job searching based on aggregate rational expectations, which is then used to analyze separately the discouraged worker effect for married/cohabiting immigrant women from non-Western countries and women born in Norway. The empirical results show that the search cost per unit of time is much higher for women born in Norway than for immigrant women. This means that an immigrant woman facing the same probability of obtaining work as a woman born in Norway is less likely to be discouraged from looking for work than a woman born in Norway. However, the actual expected search cost is higher for immigrant women than for women born in Norway. The reason for this is that the probability of obtaining an acceptable job is essentially lower for immigrant women compared to women born in Norway. Consequently, the fraction of discouraged workers is, for some groups, much higher for immigrant women than for women born in Norway, despite the fact that the search costs per unit of time for immigrant women are much lower than those for women born in Norway.
Keywords: C33; C35; J21; J22; J61; J64; 330; Discouraged workers; Aggregate rational expectations; Female immigrants; Labor force participation; Panel data; Random utility modelling